“The Skeptics Agenda” and What Science Now Says about Global Warming - Kates, Robert (Maine Policy Review, 2000)
In the Margaret Chase Smith essay, Robert Kates discusses global climate change. He notes that there is no longer any doubt that global warming is occurring, caused most likely by increased greenhouse gasses. Costs of preventing warming are mixed, and appropriate timing of such efforts is unknown, but there is no doubt that societal attention is needed for adaptation.
Keywords: global warming; global climate change